Six-Minute Walk Test in Healthy Nepalese Young Adults Aged 18 to 25 Years: A Cross- Sectional Study - Chaudhary, Shaligram; Koju, Bibek; Joshi, Lok Raj (Journal of Lumbini Medical College, 2020)
Introduction: The six-minute walk test is a simple test used to assess the exercise capacity. Variability is noted in the six-minute walk distance in different populations. Obesity also affects the six-minute walk test results. The aims of the study were to examine the relationship between body mass index and post exercise oxygen saturation and to establish a reference equation for the six-minute walk distance in young adults. Methods: A cross-sectional study was conducted with 106 subjects of age 18-25 years. The participant walked as fast as possible on a flat surface for six minutes. After a six-minute walk test, oxygen saturation and the distance walked were recorded. Results: Body mass index was negatively correlated with oxygen saturation (r=-0.587,p<0.001). Mean six-minute walk distance for males was 584.43±23.71 m and for females 469.85±30.38 m (p<0.001). Multiple linear regression analysis revealed sex and height as independent predictors of six-minute walk distance. The contributions of sex and height were statistically significant and explained 87.3% variance in the six-minute walk distance. Conclusion: Although the correlation between body mass index and oxygen saturation was statistically significant, the oxygen saturation values were still within normal range. Sex and height were the most significant predictors of the six-minute walk distance.